PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DINAS TENAGA KERJA KOTA AMBON - Ferdy Leuhery; Asiani Sijabat (Soso-Q : Jurnal Manajemen, 2020)
This research aims to determine the significant effect of motivation, work discipline on employee performance at the Ambon City Manpower Office. The method used in this research is quantitative research methods. And the sample used in this study were 45 employees. Based on the results of multiple linear regression analysis, it is found that the most dominant factor influencing employee performance. This motivation is evidenced by the largest standardized coefficient value, which is 0.650, compared to the standardized coefficient of Work Discipline, which is 0.472. Thus, motivation has a very positive and significant effect on employee performance. The better the motivation, the employee performance will increase. Work discipline has a positive effect on employee performance, meaning that if the motivation system provided is better, employee performance will increase. Kata Kunci :Motivasi , Disiplin Kerja , Kinerja Pegawai